Outcome of CNS Leukemia - A. H. Markum; M. Abdulsalam; J. Gatot; I. Wahidiyat; S. Muslichan (Indonesian Pediatric Society, 1980)
This study concerned the evaluation of CNS leukemia in relation with the necessity of maintenance prophylactic treatment of CNS leukemia, as well as prompt and intensive systemic therapy. It was performed on 77 cases of ALL hospitalized during 1974 - 1978, consisting of 44 boys and 33 girls. All were treated with Oncovin and Prednisone as induction, 6MP and MTX as maintenance and in between intrathecal MTX and CNS irradiation. Of these 77 cases, 25 developed CNS leukemia, in which 12 cases had CNS involvement on first admission while the remaining 13 cases developed this involvement during the course of the illness with the onset ranging from 1.5-29 mos. Three parameters (organomegaly, WBC of 20.000/ml, age of 5 yrs) had been evaluated in relation with the occurrence of CNS leukemia and it appeared that only W BC count correlate significantly. Our cases showed that when CNS leukemia was established at time of diagnosis the prognosis was very poor. Once a patient experienced CNS leukemia the chance to have another episode was high and it seems that maintenance prophylactic procedures of CNS leukemia is important. To prevent infiltration from the skull to the brain parenchym, it is important to start systemic treatment as early as possible.